The Clinical Significance and Potential Role of Cathepsin S in IgA Nephropathy - Zhao, Jingying; Yang, Yongchang; Wu, Yubin (Frontiers in Pediatrics, 2021)
Objective: Cathepsin S (CTSS) is an important lysosomal cysteine protease. This study aimed at investigating the clinical significance of CTSS and underlying mechanism in immunoglobulin A nephropathy (IgAN). Methods: This study recruited 25 children with IgAN and age-matched controls and their serum CTSS levels were measured by enzyme-linked immunosorbent assay (ELISA). Following induction of IgAN in rats, their kidney CTSS expression, IgA accumulation and serum CTSS were characterized by immunohistochemistry, immunofluorescence and ELISA. The impact of IgA1 aggregates on the proliferation of human mesangial cells (HMCs) was determined by Cell Counting Kit-8 and Western blot analysis of Ki67. Results: Compared to the non-IgAN controls, significantly up-regulated CTSS expression was detected in the renal tissues, particularly in the glomerular mesangium and tubular epithelial cells of IgAN patients, accompanied by higher levels of serum CTSS (P<0.05), which were correlated with the levels of 24-hour-urine proteins and microalbumin and urine erythrocytes and grades of IgAN Lee's classification in children with IgAN (P<0.01 for all). Following induction of IgAN, we detected inducible IgA accumulation and increased levels of CTSS expression in the glomerular mesangium and glomerular damages in rats, which were mitigated by LY3000328, a CTSS-specific inhibitor. Treatment with LY3000328 significantly mitigated the Ki67 expression in the kidney of IgAN rats (P<0.01) and significantly minimized the IgA1 aggregate-stimulated proliferation of HMCs and their Ki67 expression in vitro (P<0.01). Conclusions: CTSS promoted the proliferation of glomerular mesangial cells, contributing to the pathogenesis of IgAN and may be a new therapeutic target for intervention of aberrant mesangial cell proliferation during the process of IgAN.